Beliefs of Pre-Service Teachers at Elementary Teacher Education Study Program on Teaching English to Young Learners - Dinar Martia Azizah (JELLT (Journal of English Language and Language Teaching), 2023)
Abstract Based on previous research, it was revealed that teachers in elementary schools face various obstacles in implementing Teaching English to Young Learners (TEYL). In this case, research on teachers’ beliefs is needed because everything they do in class can be reflected in their beliefs toward learning. In the meantime, there has been little research on this subject. Therefore, the aim of this research is to describe the beliefs of pre-service teachers (PST) at an elementary teacher education (ETE) study program on TEYL. This research is a case study. The data was gathered by giving an open questionnaire to PST at ETE of a private universities in Yogyakarta. 95 questionnaires were gathered and then analyzed with a symbolic interactive model that started with data condensation, data display, and data conclusion/verification. The results of the study showed that the PST at ETE has a positive perspective on TEYL because it is considered to support the future of the students. The PST at ETE also believes that students have different characteristics from adult learners in learning a foreign language. In addition, PST at ETE reveals that barriers in TEYL can be caused by factors from students, teachers, and school infrastructure. To optimize TEYL, PST at ETE considered the needs of training for elementary English teachers. The implication of this research is the need for a wider opportunity for PST at ETE to implement TEYL beliefs and theory, which have been learned through real teaching practicum in the classroom. For future researchers, they could examine the connectivity between the beliefs of PST at ETE on TEYL and its implementation in teaching and learning. Keywords:belief; pre-service teacher; elementary teacher education; TEYL